Progesterone's Serum Level and a New Ultrasonographic Parameter in the First Trimester Pregnancy - Prognostic Factors for Embryonic Demise - Carmen Elena Bucuri; Razvan Ciortea; Andrei Mihai Malutan; Costin Berceanu; Maria Patricia Rada; Dan Mihu (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2019)
Abstract Objective The etiology of embryonic demise is multifactorial, with chromosomal abnormalities being the most common (40%). The purpose of the present study is to evaluate the correlation between a serum biomarker, progesterone, and an ultrasonographic parameter, the distance between yolk sac and embryo (DYSE) in assessing the prognosis of pregnancy outcome in the 1st trimester. Methods The present study is a prospective case-control analysis that includes 2 groups of patients: 81 patients with first-trimester normal evolutive pregnancy and 89 patients with embryonic demise, all of the patients having between 6 and 11 weeks of amenorrhea. Endovaginal ultrasonographic exploration was performed to evaluate the distance between the lower pole of the embryo and the yolk sac. From each subject enrolled in the study, 20ml of blood was collected for progesterone serum level measurement. Results Regarding the DYSE in the case group, lower values were observed compared with the control group, the difference being statistically significant. In the statistical analysis of serum progesterone values, statistically significant differences were observed between the 2 groups (p<0.05). Conclusion The DYSE has a high positive predictive value in identifying pregnancies with potentially reserved outcome, with the present study demonstrating that a DYSE<3mm causes an unfavorable evolution of the pregnancy. Low serum levels of progesterone are associated with an increased rate of nonviable embryos. The correlation between these two parameters increases the effectiveness of screening methods in prenatal monitoring and improves the diagnostic methods for the firsttrimester pregnancies whose outcome potential can be reserved.